Elaboración de biopelículas a partir de pectinas extraídas de cáscara de naranja (Citrus sinensis) y pulpa de café (Coffee arábica). (2023)
In the present work, the production of biofilms from a process of pectin extraction from organic material such as orange peel (C. sinensis) and coffee pulp (C. arabica) is proposed as a solution to the problem of pollution from conventional plastic. The orange is mainly used for the production of juices, this process generates a large amount of waste such as peels, pulp and seeds; In reference to coffee, in its cultivation and harvesting process, byproducts are obtained such as pulp, mucilage and lees.